Investigation of the current salt intrusion condition in the Kuantan estuary and the efficiency of the Kuantan barrage - Gisen, Jacqueline Isabella Anak; Wafty, Abd Rahman; Ahmad Amirul Faiz, Ahmad Tajudin (2019)
Kuantan River has been spotted to have a high potential rate of being affected by salt intrusion issue. A research was conducted to estimate flow discharge in the Kuantan Estuary, to test, calibrate and validate the Van der Burgh coefficient, K and dispersion coefficient, D in the 1-D analytical salt intrusion model, and to verify the salinity condition in the Kuantan Estuary before and after the construction of the barrage. Basin delineation has been done by using GIS approached in collaboration with HEC-GeoHMS. The estimation of flow discharge in the Estuary was carried out by using hydrological modelling, HEC-HMS. Besides that, the study utilised the predictive discharges from the 1-D model for comparison purposes due to data availability issues in the estuary. 1-D analytical salt intrusion model has been adopted in this study to test, calibrate and validate several parameters and the model suitability for the salinity investigation in the estuary. Thus, five field surveys have been conducted in Kuantan Estuary on 27th and 29th March, 3rd October 2017, 7th March, and 15th April 2018. The study for the estuary covered from the mouth of estuary until the reading reached 1ppt but until the Kobat barrage by using moving boat technique. In addition, the study also extended to the Belat Estuary to test the model and study the potential of the tributary. Thus, four surveys in Belat Estuary have been conducted on 26th April, 2nd October 2017, 6th March and 14th April 2018. From the salt intrusion simulation, the Van Der Burgh coefficient, K for Kuantan Estuary and Belat Estuary are 0.45 and 0.5, respectively. The dispersion in Kuantan and Belat Estuary is in the range of 100 to 250 m2/s and 50 to 200 m2/s, respectively. The future low flow in the estuaries was estimated by performing Hydrological Procedure No 12 with 7 days in 50years ARI. The low flow obtained for Kuantan and Belat Estuary is 3 and 61.5m3/s, respectively according to the fraction area. These low flow discharge then utilised in 1-D Salt Model by using the current salinity scheme. The error analyses for HEC-HMS and 1-D Salt Model are performing by using two methods which are NSE and RMSE method. In overall, the 1-D Salt Model demonstrated well in these two estuaries.